Partisipasi Organisasi Massa Dalam Pemilihan Gubernur Dan Wakil Gubernur Daerah Khusus Ibukota Jakarta Pada Tahun 2017 Perspektif Hukum Positif Dan Hukum Islam - Toni Toni; Taufiqurachman Taufiqurachman (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
It is critical to consider regional mass organizations' participation in the 2017 DKI Jakarta Regional head election. This is because regional organizations are regarded as playing a critical role in the implementation of regional head elections in various regions in the election of Governor and Deputy Governor. The Betawi Rempug Forum (FBR) was one of the regional mass organizations that took part in the DKI Jakarta Regional head election. In the Regional head election, this mass organization plays a role in supporting and succeeding the candidate pairs for governor and deputy governor. This research focuses on the participation of mass organizations in the Regional Head Election. The participation of mass organizations is important to study considering that the success of an election can be seen from the level of community participation. This study uses a qualitative method, with a literature and empirical approach. The research data were obtained from several regulations, books, articles, journals, newspapers, and phenomena in the field. The result of this research is that there is ethnic influence which is one of the factors that causes FBR to support one pair of Governor and Deputy Governor of DKI Jakarta, FBR's support is caused by the influence of figures from the pair of Governor and Deputy Governor of DKI Jakarta. Also the role of the FBR leadership affects the aspirations of the Betawi people, so that it has an impact on the progress of Betawi culture and the economy of the Betawi people.Keywords: Participation; Ormas; Regional Head Election AbstrakPartisipasi ormas daerah dalam Pilkada DKI Jakarata Tahun 2017 patut diperhitungkan. Hal ini dikarenakan dalam pemilihan Gubenur dan Wakil Gubenur, ormas daerah dinilai mempunyai peran begitu penting bagi terlaksananya Pilkada di berbagai daerah. Forum Betawi Rempug (FBR) merupakan salah satu ormas daerah yang berpartisipasi dalam Pilkada DKI Jakarta. Ormas ini berperan dalam mendukung dan mensukseskan calon pasangan gubenur dan wakil gubenur dalam Pilkada tersebut.Penelitian ini fokus pada partisipasi organisasi masa dalam Pemilihan Kepala Daerah. Partisipasi ormas penting untuk diteliti megingat keberhasilan dari sebuah pemilu dapat dilihat dari tingkat partisipasi masyarakat. Penelitian ini menggunakan metode kualitatif, dengan pendekatan literatur dan empiris. Adapun data penelitian diperoleh dari beberapa peraturan, buku, artikel, jurnal, surat kabar, dan fenomena di lapangan. Hasil penelitian ini ialah adanya pengaruh etnis yang menjadi salah satu faktor yang menyebabkan FBR mendukung salah satu pasangan Gubenur dan Wakil Gubenur DKI Jakarta, dukungan FBR disebabkan oleh pengaruh figur dari pasangan Gubenur dan Wakil Gubernur DKI Jakarta. Juga peran pimpinan FBR berpengaruh bagi aspirasi masyarakat betawi, sehingga berdampak bagi kemajuan budaya betawi maupun perekonomian masyarakat betawi.Kata Kunci: Partisipasi, Ormas, Pemilihan Kepala Daerah